Antibacterial Efficacy and Identification of Endophytic Fungal Isolates from Ocimum sanctum Leaves - Mohd Taufiq Mat Jalil; Mohd Fakharul Zaman Raja Yahya; Nurul Aili Zakaria; Kharul Azmi Muazzam Abdul Rahman; Syarifah Ab Rashid; Darah Ibrahim (HAYATI Journal of Biosciences, 2026)
The rise of multidrug-resistant (MDR) bacteria has drastically limited effective treatment options, driving the search for novel antimicrobial agents. This study evaluated the antibacterial activity of endophytic fungi isolated from Ocimum sanctum leaves and identified potential candidates with strong antimicrobial effects. Antibacterial activity was assessed through primary (agar plug) and secondary (disk diffusion) screenings, followed by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) determination using the broth microdilution method. Time-kill kinetics and scanning electron microscopy (SEM) were further employed to evaluate the extracts’ effectiveness and mechanism of action. All Gram-positive bacteria tested were susceptible to the fungal extracts, while isolate OS-93 showed no activity against Gram-negative bacteria. In the disc diffusion assay, the fermentative broth ethyl acetate extract (FBEAE) of isolates OS-64 and OS-94, and the fungal biomass methanolic extract (FBME) of OS-64, exhibited broad-spectrum antibacterial activity, inhibiting both Gram-positive and Gram-negative bacteria. The broth microdilution test revealed bactericidal effects from the FBEAE of OS-93, OS-64, and OS-94, whereas FBME of all isolates showed bacteriostatic activity. Lower extract concentrations produced bacteriostatic effects, while higher concentrations were bactericidal. Time-kill assays confirmed that shorter exposure durations were sufficient to eliminate bacteria at higher extract concentrations. SEM analysis demonstrated morphological alterations, including cavities and cell disintegration, suggesting membrane rupture as the mode of action. Morphological and molecular identification confirmed isolate OS-64 as Lasiodiplodia pseudotheobromae. These findings highlight endophytic fungi from O. sanctum as promising sources of antibacterial compounds for combating MDR pathogens.